Mowat-Wilson syndrome: literature review and case series - M. Yu. Bobylova; V. S. Kakaulina; M. O. Abramov; K. Yu. Mukhin (Русский журнал детской неврологии)
Mowat-Wilson syndrome (MWS) is a rare genetic disorder characterized by a combination of the following signs: 1) facial dysmorphism (wide nose, broad medial eyebrows, pronounced chin, and open mouth); 2) mental retardation; 3) abnormalities of internal organs (congenital heart defects, Hirschsprung's disease, hypospadias/cryptorchidism). The disease is associated with a heterozygous pathogenic mutation in the ZEB2 gene. More than 80 % of MWS patients are diagnosed with epilepsy, the onset of which is usually observed in infancy. Patents have focal motor seizures, atypical absence seizures, generalized convulsive seizures. Epileptic seizures are often triggered by fever; some children are resistant to therapy. MWS patients have a specific phenotype (blue eyes, fair hair, wide-based gait, frequent laughter, limited or absent expressive language) that requires differential diagnosis with Angelman syndrome (caused by a mutation in the UBE3A gene). MWS was described in 1998, but there have been no case reports in the Russian literature yet. We report 4 cases of MWS in children aged 2 to 13 years treated in the Svt. Luka's Institute of Neurology and Epilepsy. In all of these patients, we identified a heterozygous de novo deletion in the ZEB2 gene. Epilepsy was observed in all patients. Mean age at onset was 13 months. All children had focal motor seizures and atypical absence seizures. None of them had tonic-clonic seizures or status epilepticus. The analysis of electroencephalograms showed that patients with a lower index of epileptiform activity tend to have better development and vice versa: children with a high index of epileptiform activity during sleep had more severe developmental delay.